2016
DOI: 10.1016/j.fertnstert.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Severe spontaneous hemoperitoneum in pregnancy may be linked to in vitro fertilization in patients with endometriosis: a systematic review

Abstract: Spontaneous hemoperitoneum in pregnancy is a rare but potentially fatal complication for the pregnant woman and her unborn child. In vitro fertilization in women with severe endometriosis may be a risk factor for SHiP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 64 publications
3
68
2
Order By: Relevance
“…8 In his recent paper, Brosen et al even examined the link between endometriosis, assisted conception and SHiP and concluded that In vitro fertilization in women with severe endometriosis may be a significant risk factor for SHiP. 9 This patient did not demonstrate any evidence of endometriosis at operation. It is interesting to note that in his earlier paper Brosen et al noticed that in almost half of the affected women, diagnosis of endometriosis was previously unknown until pelvic inspection and biopsy.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…8 In his recent paper, Brosen et al even examined the link between endometriosis, assisted conception and SHiP and concluded that In vitro fertilization in women with severe endometriosis may be a significant risk factor for SHiP. 9 This patient did not demonstrate any evidence of endometriosis at operation. It is interesting to note that in his earlier paper Brosen et al noticed that in almost half of the affected women, diagnosis of endometriosis was previously unknown until pelvic inspection and biopsy.…”
Section: Discussionmentioning
confidence: 86%
“…9 Some cases were also reported during intrapartum and in the early postpartum period. [6][7][8]10 .…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that IVF in women with endometriosis increases the risk of SHiP [2] . Emerging evidence suggests that endometriosis is associated with progesterone resistance characterized by the suboptimal expression of target genes [38] .…”
Section: Mechanisms Of Ectopic Decidual Bleedingmentioning
confidence: 94%
“…This may be particularly relevant to women with endometriosis or deciduosis if they are undergoing in vitro fertilization (IVF) treatment. This dramatic complication has been associated with high perinatal morbidity and even mortality, but the trigger of the spontaneous bleeding has not been established [1,2] . Although the aetiology of SHiP remains unknown and may be multifactorial, several theories have been proposed to explain the rare complication ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The actual management of a haemoperitoneum greatly depends upon the clinical presentation, the findings at physical examination, the results from laboratory or imaging investigations, and the gestational age. Moreover, the identification of risk factors, like the use of controlled ovarian hyperstimulation for artificial reproductive techniques before pregnancy and a history of (deep) endometriosis, can be helpful in the recognition of SHiP and may affect the choice of treatment . We agree that a surgical approach is often unavoidable, but expectant management (combined with fluid resuscitation) can be considered when signs of hypovolemic shock or fetal distress are absent.…”
mentioning
confidence: 99%